Simulasi Sistem Monitoring dan Pengendalian Beban Berbasis Arduino Dengan Sensor ACS712 di Proteus - Arfian Rusdi; Nyoman Santiyadnya; I Komang Gede Sukawijana (Universitas Pendidikan Ganesha, 2026)
This research proposes a simulation-based embedded system for real-time current monitoring and automatic priority load shedding using Arduino Uno and ACS712 current sensor on Proteus software. The system addresses electrical overload issues in household installations by implementing a three-level threshold algorithm: warning (2A), low-priority shedding (2,5A), and medium-priority shedding (3,5A). Hardware components include Arduino Uno (ATmega328P), ACS712-5A (185 mV/A sensitivity), three 5V relay modules, and 20x4 LCD display. The ACS712 analog output connects to Arduino A0 pin, while relays connect to digital pins D2-D4 for priority control. The methodology follows Research and Development (R&D) approach with planning, production, and evaluation phases. Production involves C++ programming on Arduino IDE with current conversion formula: I = ((analogValue × 5.0 / 1024) - 2.5) / 0.185. Proteus simulation validates system performance through controlled current variation tests, measuring sensor accuracy (±1.5%), relay response time (<200 ms), and load shedding success rate (100%). Results demonstrate the system's effectiveness in preventing overload with 95% monitoring stability. This simulation framework contributes to smart energy management development, reducing hardware prototyping risks by 70% and providing educational prototyping platform for embedded systems (Sugiyono, 2023; Labcenter Electronics, 2023).